DERIVATIONAL MORPHOLOGY USED IN A SHORT STORY OF JOHN ROSSITER’S WIFE - Febriyanti, Febriyanti; Hajjah Zulianti (STKIP Siliwangi, 2024)
The purpose of this study is to analyze types of derivational morphology found in the short story entitled